Total hip replacement in three cats: surgical technique, short-term outcome and comparison to femoral head ostectomy - Liska, W. D.; Doyle, N.; Marcellin-Little, D. J.; Osborne, J. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2009)
Objective: To describe the surgical technique and clinical features of total hip replacement (THR) due to hip trauma in cats.Study design: Retrospective study.Sample population: Three client-owned cats that underwent THR to treat capital epiphyseal fractures, and five client-owned cats that underwent femoral head ostectomy (FHO).Methods: The clinical data included signalment, body weight, body condition score, diagnosis, implant size, surgical technique, intraoperative observations, and postoperative complications. Radiographic evaluation included implant positioning, cement mantle quality, and follow-up examination of the cement-bone interfaces. Orthopaedic examinations and client interviews were used to evaluate limb function.Results: The three cats that underwent THR had a mean body weight of 5.5 kg, a mean body condition score of 6/9, and a mean age of three years at the time of surgery. The average THR follow-up was 11 months. For the five cats that underwent FHO, the mean body weight was 6.3 kg, mean body score was 7/9, and mean age at the time of FHO was 2.5 years. The average FHO follow-up was 22 months. Hip flexion, hip extension, and thigh girth after THR compared favourably to similar measurements made after FHO. The functional outcomes after THR were excellent. The functional outcomes after FHO ranged from poor to excellent.Conclusion and clinical relevance: The recovery after THR was excellent based on clinical assessment of muscle mass, hip joint passive range of motion, gait, and owner assessment. Further blinded, randomised, and controlled trials of THR in cats are warranted.
Keywords: Cat; hip joint; total hip replacement; femoral head ostectomy